EMPATI DAN KONTROL DIRI GURU DALAM MENGAJAR DI SEKOLAH DASAR - YUFIARTI YUFIARTI; IRIANI INDRI HAPSARI; ULFATUL ANNISAA (Journal of Research and Measurement in Psychology, 2016)
This research was conducted to determine the role of empathy toward teacher's self-control in teaching at public elementary school. This research uses quantitative method. Adaptation from QCAE instruments (Cognitive and Affective Empathy Questionnaire) and self-control instruments were constructed based on Averill's theory is occupied as Empathy instruments. The sample of this research is 72 respondents, public elementary school teacher. The method used in this research is regression analysis. The result is positive influence. This shows the higher level of empathy teachers will have impact on the higher self- control. Presentation the influence result is 9,7% and rest influenced by other factors.